Penerapan Model Pembelajaran Blended Learning di Kelas V Sekolah Dasar - Eva Ardian Putri; Ibadullah Malawi; Apri Kartikasari HS (Prosiding Konferensi Ilmiah Dasar, 2022)
This study aims to improve student learning outcomes in thematic subjects of theme 4 sub-theme 2 by using a blended learning model. This research uses Classroom Action Research (CAR) with a descriptive-qualitative approach. This research was conducted at SDN Mejayan 02, Madiun Regency. The subjects of this study were fifth graders at SDN Mejayan 02, Madiun Regency, for the academic year 2021/2022, which consisted of 9 students. This research will be carried out in 2 cycles. Each cycle of classroom action research goes through 4 stages, namely: 1) planning, 2) implementation, 3) observation, 4) reflection. Data collection techniques using observation, and tests. Based on the results of the study, the results achieved in each cycle increased. In the first cycle, the percentage of students' completeness in achieving KKM 70 was 55.6% with a class average of 67.8. In cycle II, the percentage of students' completeness in achieving KKM 70 was 77.8% with a class average of 77.8. Thus, it can be seen that the implementation of the blended learning learning model can improve student learning outcomes in thematic subjects of theme 4 in class V at SDN Mejayan 02.